A case of pyogenic liver abscess in a 10-year-old girl - Jung Lim Byun; Sun Hwan Bae; Sang Woo Park (Korean Pediatric Society, 2010)
Pyogenic liver abscesses are rare in children. In pediatric patients, altered host defences seem to play an important role. However, pyogenic liver abscess also occurs in healthy children. We experienced a case of pyogenic liver abscess in a healthy immunocompetent 10-year-old-girl. The patient presented two distinct abscesses: one subphrenic and the other intrahepatic. The intrahepatic abscess resolved with percutaneous drainage and 3 weeks of parenteral antibiotic therapy but the subphrenic abscess which could not be drained needed prolonged parenteral antibiotic therapy in addition to oral antibiotic therapy. We performed follow-up serial CT scan of the abscess cavity to decide on the duration of antibiotic therapy. Here we present this case with a brief review of the literature.